Merry Go Round: a physical, virtual, physical… toy - Figueiredo, Ana Carina Pinheiro (2014)
Publicado em: "ACE 2014 : proceedings of the 11th Conference on Advances in Computer Entertainment Technology". ISBN 978-1-4503-2945-3